2008
DOI: 10.1159/000119547
|View full text |Cite
|
Sign up to set email alerts
|

The <i>Vibrio cholerae</i> Mrp System: Cation/Proton Antiport Properties and Enhancement of Bile Salt Resistance in a Heterologous Host

Abstract: The mrp operon from Vibrio cholerae encoding a putative multisubunit Na+/H+ antiporter was cloned and functionally expressed in the antiporter-deficient strain of Escherichia coli EP432. Cells of EP432 expressing Vc-Mrp exhibited resistance to Na+ and Li+ as well as to natural bile salts such as sodium cholate and taurocholate. When assayed in everted membrane vesicles of the E. coli EP432 host, Vc-Mrp had sufficiently high antiport activity to facilitate the first e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 69 publications
3
55
0
Order By: Relevance
“…2C). Notably a counterion (150 mM Cl Ϫ ) exists in this experimental system so that no ⌬ exists across the membrane (43). (b) When the ⌬pH-driven antiport activity was measured by 22 Na uptake in proteoliposomes in the absence of a counterion, the activity of the electrogenic wild type NhaA, due to its stoichiometry of 2 H ϩ /1 Na ϩ , increased dramatically in the presence of a counterion (K ϩ in the presence of valinomycin); its rate and steady state level of Na ϩ uptake drastically increased (4 -5-fold) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2C). Notably a counterion (150 mM Cl Ϫ ) exists in this experimental system so that no ⌬ exists across the membrane (43). (b) When the ⌬pH-driven antiport activity was measured by 22 Na uptake in proteoliposomes in the absence of a counterion, the activity of the electrogenic wild type NhaA, due to its stoichiometry of 2 H ϩ /1 Na ϩ , increased dramatically in the presence of a counterion (K ϩ in the presence of valinomycin); its rate and steady state level of Na ϩ uptake drastically increased (4 -5-fold) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mrp antiporters are also broadly distributed among non-alkaliphilic Gram-positive and Gram-negative bacteria and play roles in diverse physiological processes that may depend upon pH and Na ϩ homeostasis (2). In addition to Na ϩ /H ϩ antiport, several of these Mrp antiporters support resistance to anions, such as arsenite and bile salts (13)(14)(15). We hypothesize that Mrp complexes are consortiums of more than one transporter type (2).…”
mentioning
confidence: 99%
“…In contrast, antiport activities of Mrp antiporters from Bacillus species (Bs-Mrp and BpOF4-Mrp), S. aureus (Mnh) and V. cholerae (VcMrp) were rather constant or increased as pH was shifted to above pH 9.0 (DziobaWinogrodzki et al, 2009;Swartz et al, 2007). These Mrp antiporters are implicated in the tolerance of constant or transient extreme alkaline conditions in these organisms (Dzioba-Winogrodzki et al, 2009;Hiramatsu et al, 1998;Ito et al, 1999Ito et al, , 2001Kosono et al, 1999). Taken together, our results indicate that the Pha1 system has a role in the tolerance of mild alkaline conditions, rather than extreme alkaline tolerance as observed in the above-mentioned Mrp antiporters.…”
Section: Discussionmentioning
confidence: 99%
“…Mrp antiporters typically consist of six or seven membrane proteins encoded in a single operon. The mrp operons are categorized into two major groups (Swartz et al, 2005): group 1, which includes mrp from Bacillus subtilis, contains seven genes (mrpABCDEFG); and group 2, which includes Vibrio cholerae Vc-mrp, contains six genes (mrpA9CDEFG) (Dzioba-Winogrodzki et al, 2009). It has been shown that all of the components are required for the Mrp antiporter to be fully functional (Ito et al, , 2000Putnoky et al, 1998;Yoshinaka et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation